Investigating the oronasal contributions to metallic perception. (26th April 2017) - Skinner, M.; Lim, M.; Tarrega, A.; Ford, R.; Linforth, R.; Thomas, A.; Hort, J.
Abstract: Metallic taints elicited when consuming food can be unpleasant for the consumer and are therefore problematic to food manufacturers. Although metallic has been proposed as a taste in the past, evidence remains inconclusive. This study investigates the oral and nasal contributions to metallic perception using sensory evaluation and headspace analysis using gas chromatography–mass spectrometry (GC‐MS). When sniffing the headspace over divalent salt solutions, some were discriminated from water. GC‐MS did not detect volatiles in the sample headspace, one hypothesis being that sample volatiles react with phospholipids in the nasal cavity and it is lipid oxidation products which are perceived. Copper sulphate was reported as metallic when tasted with the nose occluded to eliminate retronasal perception, suggesting a gustatory or trigeminal mechanism may be involved. This work indicates orthonasal stimulation is involved in metallic perception, and contributes to the ongoing debate over metallic being a taste, trigeminal or flavour response. Abstract : Mean metallic intensity perception( +/− S.E.) for water and selected metal salts with nose open and occluded. Are these taste, aroma or trigeminal sensations or multimodal?